Transformational In Teacher Creativity - Anwar, Deni; Matin, Matin; Santosa, Heru (PT. BATARI EDU CALYA, 2024)
The researcher's aim in raising this theme is to obtain information about how much influence transformational leadership has on teacher creativity in the organization (school). The targets studied by researchers were 290 State Civil Apparatus/ Aparatur Sipil Negara (ASN) teachers in Cibitung District State Elementary Schools with a total of 38 schools. Researchers used a significance level of 5% because of the large number of samples in the Cibitung District. This research also used multistage random sampling because the State Civil Apparatus (ASN) was not evenly distributed in each school. The results of this research show that (1) there is an influence of transformational leadership on teacher creativity, (2) there is an influence of organizational climate on teacher creativity, and (3) there is an influence of transformational leadership on organizational climate.